Identity and Construction: Deconstructing the "Omnipotent" Identity in Early Childhood Teachers’ Self-concepts - He, Jing; Wang, Ping (International Journal of Social Sciences and Public Administration, 2024)
The "ideal role" in the minds of early childhood teachers is the foundation and starting point of early childhood teachers’ role research and the development of role theories. Through the questionnaire, the personality and ability characteristics of the "ideal early childhood teacher" were obtained, and the "ideal early childhood teacher" role as understood by early childhood teachers themselves was analysed. Through the questionnaire, the personality and ability characteristics of the "ideal early childhood teacher" were obtained, and the role of the "ideal early childhood teacher" as understood by early childhood teachers themselves was analysed. Drawing on the "Upland Associative Assessment Method", an associative assessment tool developed in the 1990s to assess the effects of moral education, we combined qualitative and quantitative methods to collect information on multi-dimensional role concepts at the conceptual level through the distribution of open-ended questionnaires, to obtain an appropriate amount of information on the extents of the ideal roles, and then discuss the connotations of the ideal roles of kindergarten teachers—connotation of role. The two theoretical frameworks of personality image and role cluster were used to analyse and summarise the characteristics of the "ideal kindergarten teacher" in the minds of kindergarten teachers from the collection of high-frequency vocabulary of characteristics and behavioural vocabulary, and then use the theoretical analysis to further construct the ideal personality image and the characteristics of the ideal roles in the minds of the subjects. Through the perspective of role conceptual elements, the deconstruction of the content of the ideal role of kindergarten teachers is carried out to define the dimensions of the ideal role of kindergarten teachers, describe the specific content of the ideal role of kindergarten teachers, clarify the problems related to the conceptual connotations, and effectively outline the specific meanings and basic patterns of the ideal role of kindergarten teachers.